Are Questionnaires Helpful To Predict Exercise-Induced Bronchoconstriction (EIB) And Exercise-Induced Laryngeal Obstruction (EILO)? - Dreßler, Melanie; Lassmann, Hannah; Eichhorn, Celine; Trischler, Jordis; Hutter, Martin; Zielen, Stefan; Schulze, Johannes (Klinische Pädiatrie, 2024)
Objective Exercise induced laryngeal obstruction (EILO) is an important differential diagnosis to exercise induced bronchoconstriction (EIB) and diagnosed via continuous laryngoscopy while exercising (CLE). However, availability of CLE is limited to specialized centres. And without CLE EILO is often misdiagnosed as EIB. Therefore it is essential to carefully preselect potential EILO candidates. Aim of this study was to investigate whether two short questionnaires -Asthma Control Test (ACT) and Dyspnea Index (DI) evaluating upper airway-related dyspnea- can differentiate between EIB and EILO.Methods Patients with dyspnea while exercising were analysed with an exercise challenge in the cold chamber (ECC) to diagnose EIB in visit 1 (V1), as appropriate a CLE in visit 2 (V2, 4–6 weeks after V1) and ACT and DI in V1 and V2. EIB patients were treated with asthma medication after V1.Results Complete dataset of 36 subjects were gathered. The ACT showed lower values in V2 in EILO compared to EIB patients. A lack of improvement in ACT in V2 after asthma medication of EIB patients is suspicious for additional EILO diagnosis. The DI showed higher values in V1 in EILO compared to EIB patients. A score≥30 can predict a positive CLE reaction.Conclusion ACT and DI are valuable tools in preselecting CLE candidates to assure timely diagnostic despite limited diagnostic capabilities.
Keywords: exercise induced bronchoconstriction (eib); exercise induced laryngeal obstruction (eilo); Asthma Control Test (act); Dyspnea Index (di)